MODIFIKASI MAKANAN PENUTUP BAGI TAMU YANG ALLERGEN MAKANAN - Solung, Vebry Veronika Felicia; Alelo, Maryke; Tangian, Diane (PolimdoSains, 2025)
This research involves the observation and modification of dessert products at Cempedak Private Island concerning guests who have allergies to specific foods. It explores how individuals working in the Pastry Kitchen department anticipate allergic reactions in guests by understanding food allergies and intolerances. In addition to understanding allergies, improving the provision of desserts for guests with allergies is essential. The study results in the creation of dessert products that can be enjoyed by guests with allergies, such as gluten intolerance and no dairy or dairy products. These allergens are often found in dessert products, especially those containing dairy. In conclusion, at Cempedak Private Island, kitchen standards must be enforced to ensure that all guests, including those with allergies, can safely enjoy their meals.